A Systematic Review of the Effectiveness of Knowledge Translation Interventions for Chronic Noncancer Pain Management - Maria B Ospina; Paul Taenzer; Saifee Rashiq; Joy C MacDermid; Eloise Carr; Dagmara Chojecki; Christa Harstall; James L Henry (Pain Research and Management)
BACKGROUND: Reliable evidence detailing effective treatments and management practices for chronic noncancer pain exists. However, little is known about which knowledge translation (KT) interventions lead to the uptake of this evidence in practice.